Directions for model building from asymptotic safety - Andrew D. Bond; Gudrun Hiller; Kamila Kowalska; Daniel F. Litim (Journal of High Energy Physics, 2017)
Abstract Building on recent advances in the understanding of gauge-Yukawa theories we explore possibilities to UV-complete the Standard Model in an asymptotically safe manner. Minimal extensions are based on a large flavor sector of additional fermions coupled to a scalar singlet matrix field. We find that asymptotic safety requires fermions in higher representations of SU(3) C × SU(2) L . Possible signatures at colliders are worked out and include R-hadron searches, diboson signatures and the evolution of the strong and weak coupling constants.